2015
DOI: 10.4103/0973-6247.150968
|View full text |Cite
|
Sign up to set email alerts
|

Maternal anti-M induced hemolytic disease of newborn followed by prolonged anemia in newborn twins

Abstract: Allo-anti-M often has an immunoglobulin G (IgG) component but is rarely clinically significant. We report a case of hemolytic disease of the fetus and newborn along with prolonged anemia in newborn twins that persisted for up to 70 days postbirth. The aim was to diagnose and successfully manage hemolytic disease of newborn (HDN) due to maternal alloimmunization. Direct antiglobulin test (DAT), antigen typing, irregular antibody screening and identification were done by polyspecific antihuman globulin cards and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 18 publications
0
19
0
1
Order By: Relevance
“…Anemia in newborn babies has a complex problem and has a unique blood picture due to variation in hematological profiles [6]. It can be severe to the acute life-threatening event [7]. It also causes impairment in brain development, delay in brain maturation, poor school performance and work capacity in later years, stunted growth, tissue and organ hypoxia, poorer cognitive, motor, and social-emotional development [2,8].…”
Section: Introductionmentioning
confidence: 99%
“…Anemia in newborn babies has a complex problem and has a unique blood picture due to variation in hematological profiles [6]. It can be severe to the acute life-threatening event [7]. It also causes impairment in brain development, delay in brain maturation, poor school performance and work capacity in later years, stunted growth, tissue and organ hypoxia, poorer cognitive, motor, and social-emotional development [2,8].…”
Section: Introductionmentioning
confidence: 99%
“…19 Several reports have described HDFN attributable to IgG anti-M with typical reactivity at 37°C. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Furthermore, M glycophorin is expressed on EPCs. 18 Hinchliffe et al 18 reported HDFN with pure RBC aplasia, negative neonatal DAT, reticulocytopenia, and reduced (though morphologically normal) EPCs on neonatal bone-marrow biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the review by Yasuda et al, 13 studies were identified in the literature with reports of severe hemolytic disease of the newborn based on a requirement for neonatal IVIG, red blood cell transfusion, or exchange transfusion. 4 12 16 17 18 19 20 21 22 23 24 25 26 Conversely, several studies report pregnancies complicated by anti-M alloimmunization without associated HDFN. 2 15 27 28 29 30 Notably, HDFN did not occur in approximately 400 patients with anti-M antibodies in the Netherlands and our previously reported 115 pregnancies in the United States.…”
Section: Commentmentioning
confidence: 99%